9. Effects of Low-Intensity Pulsed Ultrasound (LIPUS) on Osteoclasts and Osteoblasts: Analysis Using an Assay System With Fish Scale as a Model of Bone. Issue 8 (August 2016) - Suzuki, Nobuo; Hanmoto, Taizo; Ikegame, Mika; Furusawa, Yukihiro; Tabuchi, Yoshiaki; Kondo, Takashi; Kitamura, Kei-ichiro; Sekiguchi, Toshio; Mikuni-Takagaki, Yuko; Hattori, Atsuhiko
Abstract : Objective: Low-intensity pulsed ultrasound (LIPUS) provides noninvasive therapeutic treatment to accelerate fracture repair and distraction osteogenesis. However, most studies concerning the influence of LIPUS on bone metabolism have been conducted in vivo systems using osteoblastic cells. Therefore, details of the direct effect of LIPUS on osteoclasts are not yet fully understood. Teleost scale is a calcified tissue that contains osteoclasts and osteoblasts. Its bone matrix consists of type I collagen and hydroxyapatite, and is similar to that of mammalian bone. Therefore, we examined the effect of LIPUS on the osteoclasts and osteoblasts of zebrafish and goldfish scales, as a model of the bone matrix simplified to its bare bones. Methods: Ultrasound was generated with the Sonic Accelerated Fracture Healing System (SAFHS 4000J; Teijin Pharma, Ltd). Scales were collected from zebrafish under anesthesia; they were then treated with LIPUS for 20 minutes, incubated at 15°C for 3, 6, and 18 hours in L-15 medium, and subjected to measurement of the mRNA expression. Following the osteoclast induction by the autotransplantation of goldfish scales, we further examined the number of apoptotic osteoclasts after LIPUS treatment. Results and Discussion: At 3 hours of incubation after LIPUS treatment, osteoclastic marker expression decreased while osteoblastic markers increased. Using GeneChip analysis of zebrafish scales treated by LIPUS, we found that cell death-related genes were up-regulated by LIPUS treatment. TUNEL staining showed that the number of apoptotic osteoclasts in goldfish scales was elevated by treatment with LIPUS at 3 hours of incubation. Thus, we conclude that LIPUS promotes apoptosis in osteoclasts shortly after exposure.